Pariwisata Berbasis Komunitas sebagai Penggerak Sosial-Ekonomi Masyarakat Lokal: Strategi Pembangunan Ekowisata Bahari di Pulau Liki, Papua - R. Rachmat A. Sriwijaya; Chalfi Laroza Virginindya Sutanto; Muhammad Fauzan Ramadhani; Syifaa Aqilla Hafidz (Direktorat Pengabdian kepada Masyarakat, 2024)
Pulau Liki is one of Indonesia's outermost islands located in Sarmi Regency, Province of Papua. Situated in the midst of the Pacific Ocean, Pulau Liki possesses invaluable natural beauty, particularly the potential for its breathtaking coastal landscapes to become a promising tourist destination. Despite its unparalleled natural beauty, Pulau Liki faces challenges such as inequality, poverty, and underdevelopment. This article aims to identify the necessary preparations for achieving sustainable coastal tourism on Pulau Liki. Community Based Tourism is a proven model for developing sustainable tourism in various countries, with a focus on involving local communities in decision-making and environmental preservation. This article analyzes the role of communities in successful tourism development, especially in remote areas where the impact is felt by the local population. The study employs qualitative methods through intensive observation and the implementation of Focus Group Discussions (FGDs) to gain local perspectives on the development of tourism-based areas and the projection of CBT as a sustainable tourism development concept in Pulau Liki. The results indicate that the CBT concept is highly relevant to Pulau Liki, with the potential to enhance the well-being of the local population, protect biodiversity, and drive economic growth through Regional Original Income (PAD) and infrastructure development.